2003
DOI: 10.2527/2003.812411x
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive behavior is reduced in bulls actively immunized against gonadotropin-releasing hormone1

Abstract: The purpose of this research was to compare the frequency of aggressive behavior's in beef bulls actively immunized against gonadotropin-releasing hormone relative to contemporary nonimmunized control bulls and surgically castrated steers. Eight males were assigned to each ofthese treatments in each of 4 yr. Immunized males were treated with a GnRH-keyhole-limpet hemocyanin (KLH) conjugate at approximately 4 mo of age. A secondary (booster) immunization was administered at 12 mo. Steers were castrated at 4 mo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 14 publications
4
30
0
6
Order By: Relevance
“…From previous studies with Bopriva ® [13,20] it has been shown that body temperature increased for 1-2 days after both vaccinations without displaying any clinical signs of apathy. The above observations indicate that the ALPRO  DeLaval activity meter system represents a very sensitive tool to detect behavioral changes in bulls and confirm the results of earlier studies where behavior of vaccinated animals was subjectively assessed [6,9,13,20,40,41]. In this regard Jago et al [9] found that bulls vaccinated with the GnRF vaccine Vaxstrate  showed reduced homosexual mounting, agonistic behavior and damage to pasture, and concluded that immunocastration could provide a practical alternative to traditional methods for bull behavior control.…”
Section: Daysupporting
confidence: 87%
See 1 more Smart Citation
“…From previous studies with Bopriva ® [13,20] it has been shown that body temperature increased for 1-2 days after both vaccinations without displaying any clinical signs of apathy. The above observations indicate that the ALPRO  DeLaval activity meter system represents a very sensitive tool to detect behavioral changes in bulls and confirm the results of earlier studies where behavior of vaccinated animals was subjectively assessed [6,9,13,20,40,41]. In this regard Jago et al [9] found that bulls vaccinated with the GnRF vaccine Vaxstrate  showed reduced homosexual mounting, agonistic behavior and damage to pasture, and concluded that immunocastration could provide a practical alternative to traditional methods for bull behavior control.…”
Section: Daysupporting
confidence: 87%
“…Currently Bopriva  is the only anti-GnRF vaccine available for cattle on the market and has demonstrated good efficacy and safety in a pilot project [13] with young bulls. The latter and several other studies [6,9,20,40,41] have shown that anti-GnRF based vaccines to be efficacious at suppressing testosterone driven sexual and aggressive behavior. In these investigations behavior was only assessed subjectively but no information is available in the literature about behavior changes in vaccinated bulls analyzed objectively by using an electronic activity meter system.…”
Section: Introductionmentioning
confidence: 76%
“…Cronin et al (2003) also found that immunocastrated pigs performed less aggressive behaviour than entire male pigs. Furthermore, immunocastration has been shown to reduce aggressive behaviour in bulls (Price et al, 2003;Huxsoll et al, 1998) and bucks (Godfrey et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However, this practice affects the welfare of animals due to acute or chronic pain caused for the procedure (Rault et al 2011). Traditional castration methods are associated with high level of stress, reduction in growth rate, pain, long recovery periods (Becker et al 2012), and post-operative infections (Price et al 2003).…”
Section: Introductionmentioning
confidence: 99%